Effect of monosodium glutamate on liver of adult albino rats: a light microscopic study - Shangloo, Prenika; Syed, Midhat; Gupta, Sangeeta (International Journal of Research in Medical Sciences, 2021)
Background: Monosodium glutamate (MSG) or Aji-no-moto is the common flavouring agent which is inadvertently used in all the packed and ready to use food items. Its use has grabbed the attention with reporting of Chinese restaurant syndrome and many more side effects. This flavouring agent effects almost all the organs of the human body but the statistics regarding its ill effects are very limited, thus no objections are being raised for its use in eatables. In current study we planned to analyse the pathological effects of MSG on the liver of adult albino rats. Methods: The study was conducted on 18 inbred adult albino rats of either sex. The rats of control group (A) received only standard diet with distilled water, low dose test group (B) rats received 0.5 mg/kg of MSG dissolved in distilled water and high dose test group (C) rats received 1.5 mg/kg of MSG dissolved in distilled water per orally for 28 days. After the experimental period, the rats were sacrificed to dissect out the liver tissue which was later subjected to histological processing and tissue sectioning. Results: The liver tissue sections of the control group (A) revealed normal hepatic architecture with central veins located in the centre of the hepatic lobule and portal areas containing portal triad formed by portal venule, hepatic arteriole and bile ductile. On the other hand, the liver sections of low dose group (B) exhibited pathological changes in the form of dilated and congested central vein with sinusoidal dilatation. In high dose group (C), more marked pathological changes seen in group B along with dilatation of the portal vein was also seen. Conclusions: MSG is most widely used food additive whose safe limits for use need to be scrutinized. The current study was planned to access the minimal low dose limit of MSG for use. The observations of the afore mentioned study revealed that even small dose of MSG of 0.5 mg/kg is capable of producing pathological effects in liver which is the main site of metabolism of xenobiotics